2017
DOI: 10.1016/j.worlddev.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Technology Adoption and Employment in Less Developed Countries: A Mixed-Method Systematic Review

Abstract: The implications of technology adoption for productivity, income and welfare have been studied widely in the context of less developed countries (LDCs). In contrast, the relationship between technology adoption and employment has attracted less interest. This systematic review evaluates the diverse yet sizeable evidence base that has remained below the radars of both reviewers and policy makers. We map the qualitative and empirical evidence and report that the effect of technology adoption on employment is ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 71 publications
1
31
0
Order By: Relevance
“…Finally, the logic for the study and methodological support for the data collection and analysis is provided. (Aissaoui, 2017;Tayo et al, 2015;Ugur & Mitra, 2017). Other researchers have also examined the linkages between ICTs and the promotion of individual or community quality of life (Adera et al, 2014;Diga et al, 2013;Kariuki, 2015;Saidi & Douglas, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the logic for the study and methodological support for the data collection and analysis is provided. (Aissaoui, 2017;Tayo et al, 2015;Ugur & Mitra, 2017). Other researchers have also examined the linkages between ICTs and the promotion of individual or community quality of life (Adera et al, 2014;Diga et al, 2013;Kariuki, 2015;Saidi & Douglas, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The African realization of the Millennium Development Goals (MDGs) did not show promising results for Africa's socioeconomic development (United Nations Development Programme [UNDP], 2014); yet, researchers reported that Africa has exhibited progressing results in terms of information and communications technology (ICT) adoption (Oluwatayo & Ojo, 2018). Nevertheless, scholars argue that African developing countries still register a gap in the relationship between general ICT diffusion and innovation and socioeconomic growth and development (Asongu, Biekpe, & Tchamyou, 2019;Evans, 2019;Tayo, Thompson, & Thompson, 2015;Ugur & Mitra, 2017). For some, the impact assessment of ICT adoption toward socioeconomic development is based on economic insufficiencies among categories of people and digital divides which are often defined as differences between access and use of ICT infrastructures mostly among impoverished sub-Saharan African populations (Aissaoui, 2017;Penard, Poussing, Mukoko, & Piaptie, 2015).…”
Section: Background Of the Studymentioning
confidence: 99%
See 3 more Smart Citations